2006
DOI: 10.1523/jneurosci.3473-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Neural Coding by Two Classes of Principal Cells in the Mouse Piriform Cortex

Abstract: The piriform (or primary olfactory) cortex is a trilaminar structure that is the first cortical destination of olfactory information, receiving monosynaptic input from the olfactory bulb. Here, we show that the main input layer of the piriform cortex, layer II, is dominated by two classes of principal neurons, superficial pyramidal (SP) and semilunar (SL) cells, with strikingly different properties. Action potentials in SP cells are followed by a Ni 2ϩ -sensitive afterdepolarization that promotes burst firing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
163
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(180 citation statements)
references
References 56 publications
15
163
1
1
Order By: Relevance
“…It has been demonstrated by Suzuki and Bekkers that intrinsic AP bursting during suprathreshold depolarization is a key feature of piriform cortex pyramidal cells. In the same study, short bursts with high instantaneous firing frequencies of up to 150 Hz were evoked by strong stimulation of sensory or associative pathways with typical sensory input patterns (Suzuki and Bekkers, 2006). During sniffing, short AP bursts with instantaneous firing rates above 100 Hz have also been observed in intracellular recordings in vivo (Wilson, 1998).…”
Section: Introductionmentioning
confidence: 74%
“…It has been demonstrated by Suzuki and Bekkers that intrinsic AP bursting during suprathreshold depolarization is a key feature of piriform cortex pyramidal cells. In the same study, short bursts with high instantaneous firing frequencies of up to 150 Hz were evoked by strong stimulation of sensory or associative pathways with typical sensory input patterns (Suzuki and Bekkers, 2006). During sniffing, short AP bursts with instantaneous firing rates above 100 Hz have also been observed in intracellular recordings in vivo (Wilson, 1998).…”
Section: Introductionmentioning
confidence: 74%
“…This difference was observed not only in PC but in other brain areas such as amygdale and hippocampus (11,15). The previous studies have shown that in PC, there are interneurons classified according to the expression of two types of cell markers (molecular markers) -calcium-binding proteins and neuropeptides (23).…”
Section: Discussionmentioning
confidence: 86%
“…It obtains direct signals from the olfactory bulb (5,6,17) and processes them in different way in anterior and posterior part of the piriform cortex (10,23). The piriform cortex communicates with brain structures, such as the olfactory bulb, enthorinal cortex, amygdaloid cortex, hypothalamus, basal forebrain, brainstem, olfactory tubercle, olfactory peduncle, superior colliculus thalamus, frontal cortex, and with the hippocampus through the enthorinal cortex.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations